PEMBERDAYAAN KELOMPOK WIRAUSAHA TENUN RANGGEANG DALAM IMPLEMENTASI MANAJEMEN KEUANGAN WIRUSAHA BERBASIS SDGS DALAM UPAYA MENCIPTAKAN USAHA MANDIRI DAN MENDORONG INOVASI DAN KREATIFITAS USAHA - Tahawa, Taufik Hidayat B; Syahrir, Nurawahyuni; Galib, Abdul (Universitas Mataram, 2024)
The renggeang farmer group is one of the productive groups in producing and producing typical Mandar silk cloth. Some of the main obstacles faced by the group are limited ability for innovation and business creativity, lack of understanding of effective financial management, minimal knowledge of the concept of SDGs in entrepreneurship, limited market access and not knowing how to prepare simple financial reports. The purpose of this community service activity is to provide assistance in financial management and SDGs. In an effort to create independent businesses and encourage business innovation and creativity. The method of implementing this community service activity is training with a chronological strategy. The method of implementing activities used in this community service activity is problem identification, needs and solution analysis, training and monitoring evaluation. The results of the implementation of this community service, the independent renggeang farmer group has been running well with a positive response from all group members. The implementation of good training activities for training activities and these are expected to encourage the independent renggeang farmer group to create independent businesses and encourage business innovation and creativity.